PENGARUH KESELAMATAN DAN KESEHATAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. PANCA JAYA GARMENT KOTA PROBOLINGGO - Fandi Achmad Prasetyo; . M. Saiful Bahri; Dyah Ayu Perwitasri (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at CV. Panca Jaya Garment, Probolinggo City, the aim of this research is to examine the influence of occupational safety and health, and work discipline on employee performance at CV. Panca Jaya Garment Probolinggo. The population in this study were CV employees. Panca Jaya Garment, Probolinggo City. The sample in this research used a saturated sample technique, totaling 52 CV employees. Panca Jaya Garment, Probolinggo City. Analysis was carried out using the Multiple Linear Regression model. The results of this research show that: (1). Occupational Safety and Health and Work Discipline variables have a positive and significant influence on employee performance, (2). Discipline variables have the most dominant influence on employee performance variables.